A tale of three “cities”: Variations by site and ages in isotopic composition and mercury concentrations of Magellanic penguin during the pre-molt stage - Dodino Samanta; Riccialdelli, Luciana; Polito, MJ; Putz, Klemens; Brasso, Rebecca; Raya Rey, Andrea Nélida
Penguins are good indicators of environmental changes and respond to oceanographicconditions within their foraging grounds. We studied adult and juvenile Magellanic penguin(Spheniscus magellanicus) trophic niches using stable carbon ( 13C) and nitrogen ( 15N) isotopesand determined their feather mercury (Hg) concentrations. We sampled feathers during the premolt stage from three colonies of Tierra del Fuego with different oceanographic conditions andpopulation sizes: Staten (1,000 pairs), Martillo (5,000 pairs) and Observatorio Islands (70,000 pairs).Adults had higher δ15N and δ13C values compared with juveniles for the three colonies (p< 0.05),and occupied a higher trophic position (TP) that was reflected in their higher Hg concentration.Adults did not differ in δ15N values, while δ13C values differed significantly only between FranklinBay on Staten Island and Martillo Island. We found significantly higher adult Hg concentration and awider isotopic niche in Observatorio Island compared with Franklin Island and Martillo Island,despite their similar TP. Meanwhile, juveniles from Martillo Island had significantly higher δ13C andδ15N values relative to the other colonies. Juveniles had similar TP but differed in Hg concentration,with the lowest Hg concentrations at Martillo Island and the highest at Observatorio Island. Theseresults suggest that foraging area differences among colonies may explain the observed patterns inHg concentration and isotopic niche more so than TP. This demonstrates the plasticity of thesepenguins according to the oceanographic variability in their preferred foraging grounds anddemography with positive implications in terms of conservation under a climate change scenario. Fil: Dodino Samanta. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Riccialdelli, Luciana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Polito, MJ. State ...